Behaviour of square concrete-filled steel tubes reinforced with internal latticed steel angles under bending. (February 2023) - Wang, Jun; Li, Jun-Ru; Li, Huihui; Lv, Le-Yang
Abstract: The bending properties of square CFSTs (concrete-filled steel tubes) reinforced with internal latticed steel angles were experimentally investigated through four-point bending test, and test results of moment vs deflection curves, moment vs strain curves, bending capacity and concrete cracks were acquired, the test results showed that the latticed steel angles can restrain the cracking of concrete and delay the upwards movement of the neutral axis. After the experiment, firstly, the corresponding finite element (FE) models were established by ABAQUS and validated through comparison with test results; secondly, the bending mechanisms of the tested specimens were analysed and discussed; thirdly, the parametric analysis was conducted to investigate the influence of the main parameters, such as the yield strength and thickness of steel tube, the yield strength and area of latticed steel angles. The research results indicated that the steel tube contributed the most to the bending capacity, hence the yield strength and thickness of steel tube have the most significant influence on the bending capacity. Moreover, the design equations for the bending capacity were proposed based on the superposition method and plastic stress distribution method, and the calculation results showed that the design equations can conservatively and safely predict the bending capacity.